2022
DOI: 10.3389/fmed.2022.999215
|View full text |Cite
|
Sign up to set email alerts
|

Salivary mental stress biomarkers in COVID-19 patients

Abstract: BackgroundDuring the COVID-19 pandemic, mental health disorders and level of stress show a major increase compared to before the pandemic. Coronavirus-related stress is recently the leading cause of negative impacts on global mental health. Thus, maintaining positive mental health is as important as maintaining physical health during COVID-19. The aim of this study was to analyze salivary mental stress biomarkers as cortisol, alpha-amylase, and chromogranin A in hospitalized patients with COVID-19 to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Therefore, the potentiality of salivary ferritin levels to differentiate between the acute and the chronic phases of COVID-19 in children deserve further research. Surprisingly, we found that sAA and total protein levels were reduced in saliva of children with long COVID compared to controls, while both biomarkers use to be increased in disease (Nater and Rohleder 2009, Shaila, Pai et al 2013, Masters, Noyce et al 2015, Deneva, Ianakiev et al 2022). Nevertheless, our sAA results are consistent with previous studies showing that sAA levels decrease in both, rats and children, with chronic stress (Wolf, Nicholls et al 2008, Matsuura, Takimura et al 2012.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore, the potentiality of salivary ferritin levels to differentiate between the acute and the chronic phases of COVID-19 in children deserve further research. Surprisingly, we found that sAA and total protein levels were reduced in saliva of children with long COVID compared to controls, while both biomarkers use to be increased in disease (Nater and Rohleder 2009, Shaila, Pai et al 2013, Masters, Noyce et al 2015, Deneva, Ianakiev et al 2022). Nevertheless, our sAA results are consistent with previous studies showing that sAA levels decrease in both, rats and children, with chronic stress (Wolf, Nicholls et al 2008, Matsuura, Takimura et al 2012.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, it was surprising to observe that the levels of only two of the five biomarkers measured to evaluate the immune response, ADA2 and tADA, were significantly altered in saliva of children with long COVID compared to controls (Figure 1C). Finally, the sAA and total protein levels, that usually increased in disease (Nater and Rohleder 2009, Shaila, Pai et al 2013, Masters, Noyce et al 2015, Deneva, Ianakiev et al 2022), were significantly reduced in children with long COVID compared to controls (Figures 1D and 1E).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, the inflammatory changes post-COVID may have masked the effects of stress on salivary cortisol as nearly half of our subjects had evidence of persistent inflammation. While there is no study in post COVID subjects that assessed salivary cortisol, Deneva et al (2022) examined salivary cortisol, alpha amylase and Chromogranin A in adult hospitalized patients with COVID and demonstrated significantly high levels of these biomarkers in them.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding biomarkers of stress, the measurement of salivary alphaamylase (sAA) levels can also be very informative, since it is secreted by the parotid gland in response to sympathetic-adrenalmedullary system and increases in psychological and intense physical stress situations (Nater and Rohleder, 2009). Indeed, sAA levels are increased in COVID-19 patients, positively correlating with their mental stress scores (Deneva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%